ANALISIS STRATEGI PEMASARAN DAN KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN NASABAH - Fitriyani, Fifi (Universitas Mitra Indonesia, 2023)
This research aims to determine the influence of marketing strategies and service quality in increasing customer satisfaction (Case Study at FIF Group Federal International Finance, Bandar Lampung City). The sample in this research was FIF Group Federal International Finance customers in Bandar Lampung City, totaling 98 respondents. Primary data in this research was obtained through questionnaires distributed to respondents and secondary data in this research were sales and service elements of FIF Group Federal International Finance Bandar Lampung City. The analysis techniques used are data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. Based on the results of data analysis, it can be concluded that marketing strategy and service quality have a positive and significant effect partially and simultaneously in increasing customer satisfaction at FIF Group Federal International Finance in Bandar Lampung City.